2022
DOI: 10.3390/cancers15010134
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress and Direction of Novel Organelle—Migrasomes

Abstract: Migrasomes are organelles that are similar in structure to pomegranates, up to 3 μm in diameter, and contain small vesicles with a diameter of 50–100 nm. These membranous organelles grow at the intersections or tips of retracting fibers at the back of migrating cells. The process by which cells release migrasomes and their contents outside the cell is called migracytosis. The signal molecules are packaged in the migrasomes and released to the designated location by migrasomes to activate the surrounding cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…[6] It was further demonstrated that migrasomes spatially coordinate organ morphogenesis and promote embryonic angiogenesis in vivo, [7,8] indicating that they are distinguished from the known extracellular vesicles and their functions go beyond those of ordinary signaling vesicles like exosomes. [9][10][11] In fact, migrasomes are revealed to be imperative cell organelles that become extracellular vesicles once they detach from the retraction fibers. Migrasomes were shown to be involved in a wide range of cellular pathologies and were described as promising therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…[6] It was further demonstrated that migrasomes spatially coordinate organ morphogenesis and promote embryonic angiogenesis in vivo, [7,8] indicating that they are distinguished from the known extracellular vesicles and their functions go beyond those of ordinary signaling vesicles like exosomes. [9][10][11] In fact, migrasomes are revealed to be imperative cell organelles that become extracellular vesicles once they detach from the retraction fibers. Migrasomes were shown to be involved in a wide range of cellular pathologies and were described as promising therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%